Ivabradine reduced ventricular rate in patients with non-paroxysmal atrial fibrillation - Wanwarang Wongcharoen (2018)
© 2016 Elsevier Ireland Ltd Background It has been shown that Ifchannels can be found in AV node, apart from the sinus node. Previous animal studies showed that Ifinhibitor resulted in the rate-dependent reduction in AV node conduction during atrial fibrillation (AF). Therefore, we aimed to examine the effect of ivabradine on ventricular rate in patients with non-paroxysmal AF. Method This study was a prospective randomized, double blind, placebo-controlled study. Ivabradine, 5 mg twice a day (n = 21), or placebo (n = 11) was administered for 1 month to adult patients with non-paroxysmal AF, in addition to standard therapy. The primary end point was the change in mean ventricular rate between baseline and 1 month, as assessed by 24-hour Holter. Results The baseline characteristics did not differ between ivabradine and placebo groups (mean age was 59.7 ± 13.3 years, male 62.5%). Mean 24-hour ventricular rate at baseline was comparable between 2 groups. We found that ivabradine significantly decreased mean ventricular rate from 86.0 ± 10.9 beats/min to 79.2 ± 9.6 beats/min (p < 0.001). In contrast, no significant change in ventricular rate was observed in placebo group (84.3 ± 11.2 vs. 82.9 ± 9.9 beats/min, p = 0.469). The effect of ivabradine on rate reduction was significantly greater than placebo (6.9 ± 6.3 vs. 1.4 ± 6.0 beats/min, p = 0.024). No drug-related adverse effects were observed in both groups. Conclusion We demonstrated that ivabradine significantly decreased ventricular rate during AF compared to placebo. Therefore, ivabradine can be a potential treatment to improve ventricular control in patients with non-paroxysmal AF. Due to the small sample size, larger studies are needed to confirm this effect of ivabradine.